1997
DOI: 10.1016/s0304-3959(97)00123-1
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive performance, mood and experimental pain before and during morphine-induced analgesia in patients with chronic non-malignant pain

Abstract: This paper investigates subjective, behavioral and neurophysiological changes due to treatment with oral sustained-release morphine in six patients with severe non-malignant pain. Patients rated their mood and clinical pain on visual analog scales (VAS). Experimental pain reactions were quantified by ratings on categorical scales and evoked cerebral potentials (LEP) in response to standardized laser stimuli. A standard auditory oddball task provided reaction time (RT), errors, N1 and P2 of late auditory evoked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
84
3
9

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(99 citation statements)
references
References 16 publications
3
84
3
9
Order By: Relevance
“…The RA and FM groups reported greater use of opioid medications compared with the MSK group. However, although a variety of medications, including opioids, are known to affect cognitive function, recent data have shown that attentional functioning is either not disrupted or improves in individuals, including chronic pain patients, following opioid consumption using both performance and electrophysiological measures (17)(18)(19)(20)(21)(22). In our study, patients who received opioid medications did not perform significantly differently from patients who did not receive opioids.…”
Section: Discussioncontrasting
confidence: 49%
“…The RA and FM groups reported greater use of opioid medications compared with the MSK group. However, although a variety of medications, including opioids, are known to affect cognitive function, recent data have shown that attentional functioning is either not disrupted or improves in individuals, including chronic pain patients, following opioid consumption using both performance and electrophysiological measures (17)(18)(19)(20)(21)(22). In our study, patients who received opioid medications did not perform significantly differently from patients who did not receive opioids.…”
Section: Discussioncontrasting
confidence: 49%
“…Preliminary data suggest that pain per se leads to postoperative cognitive dysfunction in older adults (67,68). Laboratory studies performed on young and middle-aged individuals with persistent pain demonstrate that pain intensity is inversely associated with successful completion of attention-demanding tasks (28)(29)(30), and that effective use of opioid analgesics may improve cognitive status (69). These studies lend strong support to the hypothesis that pain directly impairs attention and concentration, rather than that depression acts as the mediating factor, as some investigators have suggested (70).…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that some people with chronic pain also have cognitive impairment (Kewman et al, 1991;Eccleston, 1995;Lorenz et al, 1997;Park et al, 2001;Dick et al, 2002Dick et al, , 2003Apkarian et al, 2004a;Harman and Ruyak, 2005;Veldhuijzen et al, 2006;Lee et al, 2010). Findings from a recent study in healthy individuals suggested that this cognitive impairment could be a result of the demands that pain puts on cognitive brain networks: cognitive load-related activity was enhanced by pain, and even pain alone activated this cognitive network (Seminowicz and Davis, 2007b).…”
Section: Introductionmentioning
confidence: 99%